Internalization of Islamic educational values on clean living as an effort for the formation of environmental care attitudes for elementary school students - Sutarto Sutarto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This qualitative research with a phenomenological approach aims to explore the pattern of internalizing Islamic educational values about clean living to form an attitude of caring for the environment at the Khoiru Ummah Curup Integrated Islamic Elementary School (SDIT). There were 8 informants in this study, 1 principal, 1 curriculum representative, and 6 teachers. Data collection techniques used semi-structured interviews and non-participant observation, then analyzed through four stages: data collection, data reduction, data presentation, and drawing conclusions or data verification. Checking the validity of the data using extended observations, technique triangulation, and source triangulation. The study found that the internalization of educational values about clean living to form an attitude of caring for the environment was carried out in three patterns: introduction and understanding, curriculum intervention, and habituation. The application of this pattern is expected to have an impact on students in forming attitudes and behaviors that care for the environment.